Early involvement in friendships predicts later plasma concentrations of oxytocin and vasopressin in juvenile rhesus macaques (Macaca mulatta) - Weinstein, Tamara A. R.; Bales, Karen L.; Maninger, Nicole; Hostetler, Caroline M.; Capitanio, John P. (Frontiers in Behavioral Neuroscience, 2014)
The neuropeptides oxytocin (OT) and vasopressin (AVP) are involved in social bonding in attachment relationships, but their role in friendship is poorly understood. We investigated whether rhesus macaques’ (Macaca mulatta) friendships at age one predicted plasma OT and AVP at two later time points. Subjects were 54 rhesus macaques at the California National Primate Research Center. Blood was drawn during a brief capture-and-release in the home cage, and plasma assayed for OT and AVP using an enzyme immunoassay. Separate linear mixed models for each sex tested the effects of dominance rank, age, sampling time point, housing condition, parturition status, two blood draw timing measures, and five friendship types: proximity friendships, play friendships, reciprocal friendships (a preference for a peer that also preferred the subject), multiplex friendships (friendships displayed in more than one behavioral domain), and total number of friendships. Females’ number of reciprocal and play friendships at age one significantly predicted later OT; additionally, these two friendship types interacted with rank, such that high-ranking females with the fewest friendships had the highest OT concentrations. Friendship did not predict later OT levels in males, however proximity, play, reciprocal, and total number of friendships predicted males’ plasma AVP. Play and total number of friendships also tended to predict AVP in females. Our results show that peripheral measures of neuroendocrine functioning in juvenile rhesus monkeys are influenced by early involvement in friendships. Friendships have an especially strong impact on an individual’s psychosocial development, and our data suggest OT and AVP as potential underlying mechanisms. Moreover, sex differences in the functioning of the OT and AVP systems, and their relation to friendship, may have important clinical implications for the use of OT as a therapeutic, as well as informing the social context in which it is administered.